Effect of Zn2+ Ion Concentration on the Light-Induced Scattering and Holographic Storage Properties of Zn:Cu:Fe:LiNbO3 Crystals - Zhehua Yan; Li Dai; Shunxiang Yang; Zesheng Ji; Luping Wang (Applied Sciences)
Lithium niobate (LiNbO3), a multifunctional crystalline material, has critical importance in advancing holographic storage systems. However, persistent challenges such as optical damage, limited diffraction efficiency, and slow response kinetics hinder its practical implementation. This work systematically examines the correlation between the Zn2+ dopant concentration and the defect architecture, photodamage resistance, and holographic storage properties of Zn:Cu:Fe:LiNbO3 crystals, employing advanced characterization techniques to elucidate structure–property relationships and optimize performance metrics. The experimental data reveal a pronounced Zn2+ doping concentration dependence in both photodamage resistance and holographic storage capabilities. Notably, Zn:Cu:Fe:LiNbO3 crystals doped with 7 mol% Zn2+ achieve a substantial 416-fold improvement in photodamage resistance (786.55 J/cm2) relative to the 1 mol% doped variant. Concurrently, these optimally doped crystals demonstrate superior holographic storage performance, characterized by a response time of 196.4 s, a dynamic range of 9.81, a diffraction efficiency of 66.7%, and a sensitivity of 1.04. The observed performance enhancement is fundamentally attributed to Zn2+ doping, which concomitantly suppresses intrinsic defect formation and tailors the spatial distribution of Fe3+/Cu2+ photorefractive centers within the crystal lattice. These mechanistic insights establish critical guidelines for the rational design of next-generation holographic storage materials with optimized photorefractive response and defect engineering capabilities.